Status and impacts of invasive alien plant species in Parsa National Park, central Nepal - Chaudhary, R.; Shrestha, B. B.; Thapa, H.; Siwakoti, M. (Banko Janakari, 2020)
Extent of plant invasions has been expected to be low in protected areas such as national parks due to low anthropogenic activities and high wilderness. However, recent researches across the world have revealed that plant invasions can be severe in the national parks with negative impacts on the protected species and ecosystems. Unfortunately, the status of plant invasions in the national parks of Nepal is mostly unknown. In this study, we sampled at seven locations inside the Parsa National Park (PNP) to document diversity and abundance of invasive alien plant species (IAPS) and their impacts on tree regeneration. Altogether, 130 quadrats of 10 m × 10 m were sampled. We recorded 14 IAPS in the PNP. Three of the IAPS (Chromolana odorata, Lantana camara and Mikania micrantha) were among the 100 of the world’s worst invasive alien species. C. odorata was found to be the most frequent IAPS with the highest cover. The frequency and cover of the IAPS were higher at the sites close to the settlements than at the sites away from the settlements. The species richness of the IAPS was also higher at the sites closer to the settlements than away. The sapling density of the tree species was found to have declined with the increasing cover of the IAPS suggesting that the IAPS had negatively affected tree regeneration. Our data revealed that the PNP has already witnessed massive plant invasions with widespread occurrence of three of the world’s worst invasive species. Therefore, it is high time to integrate management of invasive alien species in the management plan of the park.